Pain-related evoked potentials in patients with large, mixed, and small fiber neuropathy - Siedler, Gabriela; Sommer, Claudia; Ueceyler, Nurcan (Clinical Neurophysiology, 2020)
Objective: To investigate A-delta fiber pathways in patients with large, mixed, and small fiber neuropathies using pain-related evoked potentials (PREP).
CRIS-Team WoS Importer:2020-03-10